The Positive Impact of SFE Learning Model Assisted with Mind mapping Media Toward Students’ Knowledge Competence in Science - Bagaskara, I Made Yuda; Sudana, Dewa Nyoman; Yudiana, Kadek (Journal of Education Technology, 2020)
The problem in the low science knowledge competence in fifth-grade elementary school students at Gugus VIII, Kecamatan Kintamani, is the main research problem. The students' low science knowledge competence occurs because learning is still a teacher centre and the minimal use of learning media. Therefore, this study was conducted to analyse the effect of the student facilitator and explain (SFE) learning model assisted by Mind mapping media on science knowledge competence at fifth-grade elementary school students. This type research is a quasi-experimental design with Non-Equivalent Post-test Only Control Group Design. The population in this study were all fifth grade SD Gugus VIII Kecamatan Kintamani, consisted of 111 students. The sample in this study was taken by side random technique, it was found that the fifth grade SD Negeri Abangsongan as an experimental group which consisted of 26 students and the fifth grade of SD Negeri Suter as a control group which consisted of 25 students. Data collected used the science knowledge competency test method in multiple-choice objective tests. Science knowledge competency data analysed using descriptive statistical analysis techniques and inferential statistics with 5%. Significance level. From the data analysis results, tcount 5.76> ttable 2.00. So that H0 rejected. It means that there is a significant effect of the SFE learning model assisted by Mind mapping media on the science knowledge competence atfifth-grade elementary school students in Gugus VIII, Kecamatan Kintamani. For research that has the same variables, the results can be used as a study of relevant research.